Optics and photonics : essential technologies for our nation (National Academies Press, 2013)
Optics and photonics technologies are ubiquitous: they are responsible for the displays on smart phones and computing devices, optical fiber that carries the information in the internet, advanced precision manufacturing, enhanced defense capabilities, and a plethora of medical diagnostics tools. The opportunities arising from optics and photonics offer the potential for even greater societal impact in the next few decades, including solar power generation and new efficient lighting that could transform the nation's energy landscape and new optical capabilities that will be essential to support the continued exponential growth of the Internet. As described in the National Research Council report Optics and Photonics: Essential Technologies for our Nation, it is critical for the United States to take advantage of these emerging optical technologies for creating new industries and generating job growth. The report assesses the current state of optical science and engineering in the United States and abroad--including market trends, workforce needs, and the impact of photonics on the national economy. It identifies the technological opportunities that have arisen from recent advances in, and applications of, optical science and engineering. The report also calls for improved management of U.S. public and private research and development resources, emphasizing the need for public policy that encourages adoption of a portfolio approach to investing in the wide and diverse opportunities now available within photonics. Optics and Photonics: Essential Technologies for our Nation is a useful overview not only for policymakers, such as decision-makers at relevant Federal agencies on the current state of optics and photonics research and applications but also for individuals seeking a broad understanding of the fields of optics and photonics in many arenas.--